Groundwater salinization under the influence of paleo sea-level fluctuation: a case study in southern Laizhou Bay, China - Cui, Zhen; Chen, Guangquan; Chen, Shenliang; Yu, Hongjun; Chen, Keke; Ran, Baichuan; Fu, Tengfei; Lyu, Wenzhe; Wang, Yancheng; Jiang, Xueyan; Zhong, Xihuang (Frontiers in Marine Science, 2024)
The groundwater environment in low-lying coastal regions is significantly impacted by global sea-level fluctuation. In Laizhou Bay, three large-scale transgressions have occurred since the late Pleistocene, resulting in the transformation of ancient seawater into brine. This brine has become a major contributor to groundwater salinity in the area. This study establishes a correlation between groundwater occurrence and paleoclimate changes in Laizhou Bay using borehole sediment data. The source and mechanism of groundwater salinity are analyzed based on sediment pore water characteristics and hydrogen and oxygen isotopes. The study reveals that the stratigraphic structures in the area consist of four layers: a Holocene transgressive layer, a continental confining bed from the late Pleistocene, a Cangzhou transgressive layer from the late Pleistocene, and a fluvial aquifer from the middle Pleistocene. All aquifers in the study area have been infiltrated by modern seawater, with the uppermost Holocene aquifer influenced by evaporation and leaching processes, the central late Pleistocene aquifer remaining relatively stable, and the lower middle Pleistocene aquifer affected by subsurface low salinity runoff and exhibiting an increasing trend with depth. Given the presence of numerous hydrogeological environments globally that are similar to the study area, the obtained mechanisms of groundwater salinization in this study will provide theoretical support for groundwater management in similar regions worldwide.